Pengaruh Work From Home Dan Stres Kerja Terhadap Kinerja Guru Sman 1 Manonjaya Selama Masa Pandemi Covid-19 - Zakiatul Mukaromah (J-CEKI : Jurnal Cendekia Ilmiah, 2022)
Work From Home is a new work system during the current covid-19 pandemic, namely working from home to avoid crowds and comply with Indonesian government regulations. Job Stres is a condition where a person experiences tension due to conditions that affect himself. Teacher performance is the ability of a teacher to carry out tasks in learning at school and is responsible for students who are under his guidance by improving student achievement or learning outcomes. This study aims to determine the effect of Work From Home and work Stres on teacher performance at SMAN 1 Manonjaya during the Covid-19 pandemic. This study uses a quantitative approach with a descriptive type of research. The hypothesis in this study was tested using Multiple Linear Regression. The object of this research is the teacher of SMAN 1 Manonjaya. The census in this study amounted to 70 people. The results of this study indicate that Work From Home has a significant effect on teacher performance at SMAN 1 Manonjaya, while work Stres has no significant effect on teacher performance at SMAN 1 Manonjaya